Physiological demands of jockeys in relation to injury risk, performance, and career longevity : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at School of Veterinary Sciences, Massey University, Manawatu, Aotearoa, New Zealand - Legg, Kylie (Massey University, 2022)
Jockeys work at close to their physiological capacity during a race. However, despite the pivotal role of the jockey in the success of racing, there are limited data published on the physiological challenges of race riding and the influence of muscular fatigue on the jockeys during a race and over their careers. Until the sport-specific physiological demands of race riding are quantified, the development of evidence-based sport specific and potentially performance enhancing jockey training programmes cannot be realised. Successful training interventions require knowledge of the physiological demands and performance characteristics of the specific sport. Therefore, the aims of this thesis were to characterise the injury risk, performance and career longevity of jockeys in relation to their overall and specific, training and competition level physiological demands. Using race-day records of 786 jockeys riding over 14 years (2005 – 2019) of Thoroughbred racing in New Zealand (n = 421,596 starts), descriptive statistics, uni- and multi- variable analyses and Kaplan Meier survival curves, it was determined that jockeys with higher competitive workloads performed better, had fewer falls and longer careers than those with lower competitive workloads. A nationwide online survey completed by 40% of the jockey population in New Zealand identified that the main form of exercise for jockeys was riding in training and racing. This indicated that jockeys with higher competitive workloads may have a greater degree of sport specific fitness from regular competitive riding that jockeys with lower workloads (or apprentice jockeys beginning their career) are unable to gain through simply riding track-work and trial rides. The ride specific physiological demands, body displacements and muscle activities of jockeys were determined by instrumenting jockeys with heart rate (HR) monitors, global positioning system (GPS), accelerometers (body displacement) and electromyographic clothing (recording eight muscle groups: quadriceps, hamstrings, gluteal, lower back, obliques, abdominal, trapezial and pectoral) during a typical day at track-work, trials, and races. The physiological (aerobic) demands of riding increased from low during track-work, to moderate when riding trials, and near-maximal during race-riding. Race-riding jockeys adopted a lower crouched posture with greater hamstring activation than jockeys riding track-work or trials. These studies provide evidence that jockeys need more specificity in training for competitive race-riding. Future studies could use these data to model the optimum level of competition specific fitness for a jockey to maintain to both reduce injury risk and optimise performance, which would in turn, enhance the career longevity of jockeys.
The chapters reported in this thesis were completed during candidature. Permissions were granted from each of the corresponding journals to publish the outputs in this thesis.
Listed in 2023 Dean's List of Exceptional Theses
Keywords: Jockeys; Health and hygiene; Physiology; New Zealand; Dean's List of Exceptional Theses; 420702 Exercise physiology; 420604 Injury prevention